The justifiability of France's 'burqa ban', considering the limitation clauses of Article 9 of the European Convention on Human Rights under European Public Order - Kvedova, Dženeta (Riga Graduate School of Law, 2018)
This thesis analyzes prohibitions on wearing the burqa (commonly referred to as “the burqa ban”) within the context of Article 9 (freedom of thought, conscience and religion) of the European Convention on Human Rights. The main objective of this thesis to, considering the rule of law, identify any legal issues with the burqa ban, as well as evaluate the judicial application and the legal intricacies within the limitation clauses enshrined under Article 9(2) of the Convention.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; European Convention on Human Rights